SUBSTRATE VOLUME AND NURSERY TIMES FOR EARLINESS AND YIELD OF GREENHOUSE TOMATO - Martínez-Gutiérrez, Gabino A.; Morales, Isidro; Aquino-Bolaños, Teodulfo; Escamirosa-Tinoco, Cirenio; Hernández-Tolentino, Martín (Emirates Journal of Food and Agriculture, 2017)
In nurseries, seedling management can be an option to increase the yield and earliness of the harvest of Solanum lycopersicum L. in the greenhouse. The objective of this study was to evaluate substrate volumes and days in nursery of tomato seedlings evaluating root and seedling height, as well as, their effects on harvest earliness and yield. Two independent and consecutive experiments were carried out. The first experiment was done in the nursery where the volumes 22, 100, 150, 250, 350 and 450 cm3 substrate and, 30, 40, 50 and 60 nursery days were evaluated. The control was 22 cm3 and 30 days. The variables evaluated were: Seedling height, stem diameter, length and volume of the root and fresh and dry root weight. The second experiment was the cultivation of seedlings in composted maguey bagasse, agrolite and the normal soil as the control. The response variables were days till harvest after transplanting and total yield. Both experiments were conducted in a randomized complete block, with three repetitions and twenty plants per experimental unit. In the nursery, all variables increased with the increasing of substrate volume and nursery time. In cultivation, the highest total yield (8.20 kg plant-1) were obtained with seedlings produced with 22 cm3 volume of substrate and 30 nursery days. Seedlings with substrates volumes greater than 100 cm3 and more than 40 days in the nursery began the fruit ripening and harvest 60 days after transplantation. The control initiated it at 90 days.